The midnight train - Haig, Matt, 1975- (Viking, 2026)
"When your life flashes before your eyes, where would you stop? No one can change the past, but the Midnight Train can take you there. The chance to re-live the moments that meant most. To see what kind of person you really were. For Wilbur his best days were with Maggie, the love of his life. On his honeymoon in Venice. Before he gave it all away. He wishes he could go back and live differently. But to do so risks everything . . . A magical, time-travelling love story, from the world of The Midnight Library"--